Planeamiento estratégico para mejorar la eficiencia y la competitividad de la empresa de transportes antonella s.r.l. de chimbote: 2009-2010 - Vera Mondragón, Manuel Antonio (2014)
This research aims to design a main indicator system for evaluation and selection of an independent auditor, to consider the fundamentals and specify the variables and indicators to make it viable. The population as a whole formed professional accountants who were interested in participating in a tender for the selection of independent auditors audit firm convened a qualified and registered for the contest. The sample was constituted by the set of stakeholders confirmed and participated in the evaluation process. The system was developed based on aspects Social Responsibility, Professional Certification and Ethical Principles, which are essential in the evaluation. The aspects mentioned are the variables of work, the same that were broken into a series of twenty-defined indicators, determining thresholds for application. The results show that 8.33% of the total sample achieved positive scores, which demonstrates the need for aspiring professional auditors to form and train according to the requirements of the quality standards that the market determines, and basically include Social Responsibility, Professional Certification and Ethical Principles.